Development of Smart pH-Sensitive Collagen-Hydroxyethylcellulose Films with Naproxen for Burn Wound Healing - Elena-Emilia Tudoroiu; Mădălina Georgiana Albu Kaya; Cristina Elena Dinu-Pîrvu; Lăcrămioara Popa; Valentina Anuța; Mădălina Ignat; Emilia Visileanu; Durmuș Alpaslan Kaya; Răzvan Mihai Prisada; Mihaela Violeta Ghica (Pharmaceuticals)
Background: Developing versatile dressings that offer wound protection, maintain a moist environment, and facilitate healing represents an important therapeutic approach for burn patients. Objectives: This study presents the development of new smart pH-sensitive collagen-hydroxyethylcellulose films, incorporating naproxen and phenol red, designed to provide controlled drug release while enabling real-time pH monitoring for burn care. Methods: Biopolymeric films were prepared by the solvent-casting method using ethanol and glycerol as plasticizers. Results: Orange-colored films were thin, flexible, and easily peelable, with uniform, smooth, and nonporous morphology. Tensile strength varied from 0.61 N/mm2 to 3.33 N/mm2, indicating improved mechanical properties with increasing collagen content, while wetting analysis indicated a hydrophilic surface with contact angle values between 17.61° and 75.51°. Maximum swelling occurred at pH 7.4, ranging from 5.65 g/g to 9.20 g/g and pH 8.5, with values from 4.74 g/g to 7.92 g/g, suggesting effective exudate absorption. In vitro degradation proved structural stability maintenance for at least one day, with more than 40% weight loss. Films presented a biphasic naproxen release profile with more than 75% of the drug released after 24 h, properly managing inflammation and pain on the first-day post-burn. The pH variation mimicking the stages of the healing process demonstrated the color transition from yellow (pH 5.5) to orange (pH 7.4) and finally to bright fuchsia (pH 8.5), enabling easy visual evaluation of the wound environment. Conclusions: New multifunctional films combine diagnostic and therapeutic functions, providing a promising platform for monitoring wound healing, making them suitable for real-time wound assessment.